Expression, Purification, and Evaluation of Diagnostic Potential and Immunogenicity of a Recombinant NS3 Protein from All Serotypes of Dengue Virus - Laura Mónica Álvarez-Rodríguez; Angel Ramos-Ligonio; José Luis Rosales-Encina; María Teresa Martínez-Cázares; Aurora Parissi-Crivelli; Aracely López-Monteon (Journal of Tropical Medicine)
Dengue is one of the major public health concerns in the world. Since all the four serotypes are actively circulating in Mexico, there is a need to develop an efficient diagnosis system to improve case management of the patients. There exist few studies evaluating the use of the NS3 protein as a protective antigen against dengue virus (DENV). In this paper we show the expression of a recombinant NS3 protein from all serotypes of dengue virus (GST-DVNS3-1-4) and report a reliable “in-house detection system” for the diagnosis of dengue infection which was field-tested in a small village (Tezonapa) in the state of Veracruz, Mexico. The fusion proteins were immunogenic, inducing antibodies to be able to recognize to antigens up to a 1 : 3200 dilution. The purified proteins were used to develop an in-house detection system (ELISA) and were further tested with a panel of 239 serum samples. The in-house results were in excellent agreement with the commercial kits with κ=0.934±0.064 (95%  CI = 0.808–1.061), and κ=0.872±0.048 (95%  CI = 0.779–0.965) for IgM and IgG, respectively. The agreement between the NS1 antigen detection versus the rNS3 ELISA, κ=0.837±0.066 (95%  CI = 0.708–0.966), was very good. Thus, these results demonstrate that recombinant NS3 proteins have potential in early diagnosis of dengue infections.